Toward controlling the Al2O3/ZnO interface properties by in situ ALD preparation. Issue 24 (7th June 2022) - Janowitz, Christoph; Mahmoodinezhad, Ali; Kot, Małgorzata; Morales, Carlos; Naumann, Franziska; Plate, Paul; Zoellner, Marvin Hartwig; Bärwolf, Florian; Stolarek, David; Wenger, Christian; Henkel, Karsten; Flege, Jan Ingo
Abstract : The electronic band alignment of an alumina/zinc oxide thin-film heterostructure solely grown by atomic layer deposition has been determined by XPS/UPS depth profiling, correlating the electronic properties with the interface chemical composition. Abstract : An Al2 O3 /ZnO heterojunction was grown on a Si single crystal substrate by subsequent thermal and plasma-assisted atomic layer deposition (ALD) in situ . The band offsets of the heterointerface were then studied by consecutive removal of the layers by argon sputtering, followed by in situ X-ray photoelectron spectroscopy. The valence band maximum and conduction band minimum of Al2 O3 are found to be 1.1 eV below and 2.3 eV above those of ZnO, resulting in a type-I staggered heterojunction. An apparent reduction of ZnO to elemental Zn in the interface region was detected in the Zn 2p core level and Zn L3 MM Auger spectra. This suggests an interface formation different from previous models. The reduction of ZnO to Zn in the interface region accompanied by the creation of oxygen vacancies in ZnO results in an upward band bending at the interface. Therefore, this study suggests that interfacial properties such as the band bending as well as the valence and conduction band offsets should be in situ controllable to a certain extent by careful selection of the process parameters.